A PRELIMINARY ACCOUNT OF THE FISHERIES OF VIZHINGAM - Gopalan Nayar, S. (Indian Journal of Fisheries, 2015)
As a part of the research programme of the Central Marine Fisheries Research Station, it was decided in 1948 to conduct a survey of the Indian coastline to estimate the marine fish landing s,and to find out the types of fish stocks available. As very little work (Bal and Banerji, 1951) has been done in the past regarding the fishery resources of our country, a preUminary survey was found essential before embarking on the final programme. With this in view, the author conducted a preliminary survey in 1949 to ascertain the number of fishing villages, boats, nets and fishermen along the coastal strip extending from Cape Comorin in the south to Ponnani River in Malabar District in the north. Based on the data thus collected, the final design to estimate the landings was made. Initially five observation centres, Blangad in South Malabar, Narakkal and Malippuram in Trichur District, Wadi in Quilon District, and Vizhingam in Trivandrum District, of the erstwhile Travancore-Cochin State, were selected. Regular observations were taken at these centres in 1950.